Avaliação da qualidade de calçadas no entorno da Avenida Brás de Aguiar em Belém/PA sob o método IQC - FARIAS, Matheus Kaique Ferreira (2020)
The Brazilian law 12.587/12, associated with the Brazilian Traffic Code, assures pedestrians as priority in urban areas, since it prioritizes travel by non-motorized transport. Therefore, the quality of sidewalks should be an essential theme for urban planning. However, public authorities clearly do not guarantee this reality to be true, given that, in most Brazilian urban centers, the pathways exhibit unsatisfactory configurations. Accordingly, the present work aims to evaluate the level of service of the pathways located at Avenida Comandante Brás de Aguiar and its crossings, between Nazaré and Gentil Bittencourt avenues, a region located in the neighborhood of Nazaré, Belém/PA. Therefore, the IQC method – Indice de Qualidade de Calçadas, developed by Ferreira and Sanches (2001), was used in the present work. This method is performed through an on-site technical analysis of five quality indicators, coupled with an assessment of pedestrian perception. Thirty-four sidewalk sections were investigated and 70 pedestrians were interviewed. Through this research, it was found that most of the studies pathways displayed satisfactory results - 91% of them had excellent or good performance, while 9% had regular performance. Only 3 sections were at service level B, 28 at level C and the remaining 3 at level D; no sections were in the A, E and F service levels. The best sidewalks were around the intersection of Av. Brás de Aguiar and Tv. Dr. Moraes, while the worst were at Tv. Rui Barbosa and Av. Generalissimo Deodoro. In addition, it was found that effective width was the quality indicator that most concerns users. Given the small number of respondents and the subjectivity of the technical assessment, additional assessments were made, (i) comparing the present study with another one done at the central region of the city, (ii) evaluating different scenarios with different weights and (iii) performing an analysis of sensitivity of quality indicators. Through these analyzes it was verified the robustness of the method, since it explained the superiority of the quality of the Brás sidewalks, when compared to the commercial ones. Moreover, when the other analyzes were made, there was little significant variation in the results.